Responsible Management and Use of Data in UN Peace Operations - Oksamytna, Kseniya (International Peace Institute, 2023)
In recent years, the UN has embarked on an ambitious project to use data more extensively and effectively to improve the safety of peacekeepers and the implementation of peace operations’ mandates.
Keywords: 2023-10 October